Memory scrutinized through electrical brain stimulation: A review of 80 years of experiential phenomena. (July 2017) - Curot, Jonathan; Busigny, Thomas; Valton, Luc; Denuelle, Marie; Vignal, Jean-Pierre; Maillard, Louis; Chauvel, Patrick; Pariente, Jérémie; Trebuchon, Agnès; Bartolomei, Fabrice; Barbeau, Emmanuel J.
Highlights: The electrical parameters that reliably induce reminiscences remain to be specified. Memory networks can only be activated by some of their nodes: mostly temporal. The electrical parameters that reliably induce reminiscences remain to be specified. Abstract: Electrical brain stimulations (EBS) sometimes induce reminiscences, but it is largely unknown what type of memories they can trigger. We reviewed 80 years of literature on reminiscences induced by EBS and added our own database. We classified them according to modern conceptions of memory. We observed a surprisingly large variety of reminiscences covering all aspects of declarative memory. However, most were poorly detailed and only a few were episodic. This result does not support theories of a highly stable and detailed memory, as initially postulated, and still widely believed as true by the general public. Moreover, memory networks could only be activated by some of their nodes: 94.1% of EBS were temporal, although the parietal and frontal lobes, also involved in memory networks, were stimulated. The qualitative nature of memories largely depended on the site of stimulation: EBS to rhinal cortex mostly induced personal semantic reminiscences, while only hippocampal EBS induced episodic memories. This result supports the view that EBS can activate memory in predictable ways in humans.